Epiphonies of Motivation and Emotion Throughout the Life of a Cellist - López-Íñiguez, Guadalupe (Southern Illinois University, Edwardsville, 2019)
This layered autoethnography comprises momentary scenes connected to musical pieces for cello that are engraved in my memory and on the calluses of my fingertips by significant physical, emotional, and motivational experiences that have accompanied me since my youth. My artful methodology invokes truthful memory through sound to compose a “methodology of the heart” (Pelias 2004). I thus blend music “epiphonies” and stories with past and present moments to create a thickness of duration, an épaisseur. I purposely used intersubjectivity as an evocative sensitivity when analyzing autobiographical memories to interpret cultural assumptions in the field of music education and classical music performance. These assumptions include the importance of being ‘talented’, the exposure to external stressors and competitiveness, and the imbalance of power relations between teachers and students. My aim is to expand understandings of forms of arts research, and to highlight certain pedagogical and social practices in the education of classical musicians that can compromise their well-being and identity construction.
Keywords: music; music education; musicians; emotions; cognition